Agile Processes in Software Engineering and Extreme Programming : 19th International Conference, XP 2018, Porto, Portugal, May 21–25, 2018, Proceedings /: 19th International Conference, XP 2018, Porto, Portugal, May 21–25, 2018, Proceedings. (2018) - Unknown
No abstract available